Organizational context variables to be considered in the reward system design oriented to product innovation - Marx, Roberto; Soares, João Paulo Reis Faleiros; Barros, Lidyane Stephane da Silva (Review of Business Management, 2016)
Purpose – The main purpose of this paper is to discuss some key variables to be taken into consideration in an organizational context when designing reward systems focused on maximizing product innovation. In addition to identifying such variables, the paper aims to understand how each of them can influence this design. Design/methodology/approach – Based on existing literature, a reference chart was created using context variables (organizational strategy, type of innovation, beliefs and cultural traits, and previously established systems of goals and rewards) and their implications on the reward system design. A field research was conducted through qualitative interviews with five specialists, consultants, and scholars in strategic human resource management and reward systems, as well as case studies on four large-scale industrial companies known for being innovative. Findings – The research has shown that little knowledge has been accumulated by specialists as well as by designers of reward systems at organizations operating in Brazil concerning the issue studied. Moreover, the four main previously listed variables were maintained, and the field research allowed a series of analyses that changed relevant aspects of the details of that chart. Originality/value – This paper can contribute to fulfill the gap existing in literature on the reward system design, and proposes a reference chart that can assist the designer in elaborating it.